The needs and preferences of general practitioners regarding their CPD learning: a Free State perspective - J. Botes; J. Bezuidenhout; W. J. Steinberg; G. Joubert (South African Family Practice)
Background: The Health Professions Council of South Africa (HPCSA) requires all registered Health Practitioners in South Africa to complete accredited learning opportunities, and provide proof thereof. CPD is the chosen model, which focuses on holistic development of the professional. The UFS Department of Family Medicine presents refresher courses for general practitioners, covering all relevant ﬁelds of interest.